2022
DOI: 10.1111/ans.17514
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic workup and laparoscopic approach for median arcuate ligament syndrome

Abstract: Background: Median arcuate ligament syndrome (MALS) is a rare disorder characterized by the compression of the coeliac trunk and plexus by fibrous arches of the median ligament. It commonly occurs in young women with postprandial epigastric pain, weight loss and nausea. We present a single surgeon experience on the diagnostic approach and management of MALS with a focus on laparoscopic surgery. Methods: A retrospective review of adult patients diagnosed with MALS during a 10-year period (2011-2021) was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The first description of a laparoscopic MAL release was in 2000 by Roayaie et al [ 21 ]. After their original report, other groups reported their experience in small single-institution case series [ 4 , 8 , 11 , 12 ]. A main concern of the laparoscopic approach is uncontrolled bleeding, reported in 9.1% of cases, necessitating a rapid conversion to a laparotomy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first description of a laparoscopic MAL release was in 2000 by Roayaie et al [ 21 ]. After their original report, other groups reported their experience in small single-institution case series [ 4 , 8 , 11 , 12 ]. A main concern of the laparoscopic approach is uncontrolled bleeding, reported in 9.1% of cases, necessitating a rapid conversion to a laparotomy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure can be done open, laparoscopic or more recently robotic-assisted. However, there is not enough evidence to help guide surgeons as to which operative approach is superior over the other, with limited data coming from single-institution series [ 4 , 7 , 8 , 11 16 ]. In the largest study to our knowledge, no difference was found in postoperative outcomes between the laparoscopic and open approach [ 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation